TESS observations of southern ultrafast rotating low-mass stars. Issue 2 (11th July 2020) - Ramsay, Gavin; Doyle, J Gerry; Doyle, Lauren
ABSTRACT: In our previous study of low-mass stars using TESS, we found a handful that show a periodic modulation on a period <1 d but also displayed no flaring activity. Here we present the results of a systematic search for ultrafast rotators (UFRs) in the Southern ecliptic hemisphere, which were observed in 2-min cadence with TESS . Using data from Gaia DR2, we obtain a sample of over 13 000 stars close to the lower main sequence. Of these, we identify 609 stars that lie on the lower main sequence and have a periodic modulation <1 d. The fraction of stars that show flares appears to drop significantly at periods <0.2 d. If the periods are a signature of the rotation rate, this would be a surprise, since faster rotators would be expected to have a stronger magnetic field and, therefore, produce more flares. We explore possible reasons for our finding: The flare inactive stars are members of binaries, in which case the stars rotation rate could have increased as the binary orbital separation reduced due to angular momentum loss over time, or that enhanced emission occurs at blue wavelengths beyond the pass band of TESS . Follow-up spectroscopy and flare monitoring at blue/ultraviolet wavelengths of these flare inactive stars are required to resolve this question.